The Effect of English Literature in Perfection of English Language Performance of Secondary Schools Students in North Kordofan State, Sudan - Abdu-Elrahman, Abdu-Elrahman Elshreef (IJRDO- Journal of Educational Research, 2017)
The current study was conducted in North Kordofan State during 2015-2016.The objectives of the study were to access the effect of using literature in the language classroom, to improve learners’ language skills of secondary schools students. Study problem was the deterioration of secondary school student’s level in English language. The primary data were collected via structured questionnaire distributed randomly to 60 teachers of long teaching careers. Descriptive statistic was used for data analysis, and results presentation. Study found that, the using of English literature in classroom helps secondary schools students better understanding of other cultures (73.1%), the use of English literature improved students English language levels (67.3%), the effectiveness of using English literature in classroom, develop excellent opportunities to express themselves in (63.5%).Study recommended Federal ministry of education should have to include literature in curriculum of secondary school.